Ticagrelor versus clopidogrel after intracranial stent angioplasty: a real-world study - Sun, Lili; Wang, Shuzhen; Song, Yun; Zhao, Wei; Zheng, Meimei; Yin, Hao; Zhang, Jun; Meng, Yao; Wang, Wei; Han, Ju (Frontiers in Neurology, 2023)
Objective It was unknown whether a regimen of aspirin plus ticagrelor (aspirin-ticagrelor) attenuates ischemic vascular events without increasing bleeding risk in patients who had undergone intracranial stenting compared with an aspirin plus clopidogrel (aspirin-clopidogrel) regimen. This article compares the efficacy and safety outcomes of the two double antibody regimens in patients undergoing intracranial stent and investigates whether aspirin-ticagrelor could be an alternative antiplatelet agent without increasing the risk of bleeding. Methods We conducted a retrospective analysis of our database for patients who had undergone intracranial stenting. From January 2017 to May 2021, consecutive patients treated with endovascular stenting were identified and dichotomized by whether aspirin-ticagrelor or aspirin-clopidogrel were used. The outcomes were compared by propensity score matching. Results A total of 340 patients treated with intracranial stent were included. Of all, 132 patients were matched. At 180 days, ischemic vascular events occurred in one patient (1.5%) in the aspirin-ticagrelor group and in six patients (9.1%) in the aspirin-clopidogrel group. Although the absolute incidence of ischemic vascular events [1.5% (1/66) vs. 9.1% (6/66), p = 0.125] was lower in the aspirin-ticagrelor group than in the aspirin-clopidogrel group, there were no statistical differences. There were no statistical differences in ischemic vascular events, ischemic stroke, or death up to 180 days between the two groups. In addition, the incidence of bleeding did not differ. No intracranial hemorrhage or mild bleeding occurred. No statistically significant difference was noted in restenosis and symptomatic restenosis at follow-up. Conclusion In our study involving patients with acute ischemic stroke who had undergone intracranial stenting, aspirin-ticagrelor was not found to be superior to aspirin-clopidogrel in reducing the rate of ischemic vascular events. The risk of bleeding did not differ between the two groups. Aspirin-ticagrelor does not lower total restenosis and symptomatic restenosis risk at follow-up.